Cr3+-activated Na3X2Li3F12 (X = Al, Ga, or In) garnet phosphors with broadband NIR emission and high luminescence efficiency for potential biomedical application. Issue 42 (20th October 2021) - Nie, Wendong; Li, Yan; Zuo, Jiaxing; Kong, Yankui; Zou, Wanfang; Chen, Guang; Peng, Jiaqing; Du, Fu; Han, Lei; Ye, Xinyu
Abstract : We report three isotypic garnet Na3 X2 Li3 F12 (X = Al, Ga, or In) phosphors with intense and stable NIR luminescence. They have great application potential in the biomedical field. Abstract : With the rapid development of NIR pc-LEDs, the development of a novel NIR phosphor with broadband emission, strong luminescence and high thermal stability is urgent. Here, three isotypic garnet fluorides Na3 X2 Li3 F12 (X = Al, Ga, or In) (NXLF) activated by Cr 3+ were synthesized. The emission peak shifts from 752 to 778 nm and FWHM expands from 101 to 121 nm. The values of Dq / B indicate that Cr 3+ ions undergo a weak crystal field. Among them, NInLF:Cr 3+ has the highest IQE of 87.2% and NAlLF:Cr 3+ exhibits the best thermal stability, which maintains 82% of its initial intensity at 423 K. The Huang–Rhys factor of NAlLF:Cr 3+ exhibits a rather low EPC. The output power and photoelectric conversion efficiency of the packaged NIR pc-LEDs could achieve 149 mW and 14.3% at 350 mA. Under the irradiation of NIR light, clear images of blood vessel distribution of palm and arm were obtained, implying that these phosphors have great application potential in the biomedical field.